Changesin Myoglobin of Big Eye Tuna During Chilling Storage - Stevi Imelda Murniati Wodi; Wini - Trilaksani; Mala - Nurilmala (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Big eye tuna (Thunnus obesus) is one of the species of tuna which is have some value added such as have potential to improve animal protein sources, have high economic values as well as an export commodity.Mishandling and misapplication of high temparatures on the tuna handling at the tropics and sub tropics climate was significantly decreasing the value of myoglobin and affecting the solubility of protein. Myoglobin is a globular protein that have small molecular weight size and it was an important factor for determining the quality of meat and influencing factors of purchasing power by the consumer. The purpose of this experiments is to determining the changes of myoglobin content and the water soluble proteins content at some parts of big eye tuna in 9 days chilling temperatures. The portion which is analized was the ventral area, dorsal area and tail area. Myoglobin content in all portion above, both light and dark meat was analized. The results shows the decreased value of myoglobin content from first handling (day zero) until day ninth (days 9th) experiment. Each myoglobin contentfrom white meat at at ventral, dorsal and tail meat was decreased from 121.68 mg/100 into 41.35 mg/100, 148.2 mg/100g into 52.01 mg/100g, 105.16 mg/100g into 31.34 gr/100gram, after day ninth. The myoglobin content from dark meat at ventral, dorsal and tail meat, was decreased, too ; from 418.64 mg/100 gr into 121.01 mg/100 g, 446.21 mg/100 g into 58.34 mg/100 r and 145.65 mg/100 gr into 87.98 mg/100g after day ninth.Water soluble protein was derived into protein bands with molecular weight 15,4 kDa and 14 kDa. Its suspected as the myoglobin protein. The molecular weight difference was caused from degradation of protein during the storage.Keywords: Big eye tuna, meat, storage, myoglobin